Search and research of energy-efficient configuration of the power supply network - Negadaev, V.A. (EAI Endorsed Transactions on Energy Web, 2019)
Model of main structure of power-supply is considered for research of states of working collections of induction motors. Model consists of separate electromechanic modules, which can contain different amount of motors. Modules are connected in different points to main cable, laid from transformer before remoted module. On base of this model is developed software program, intended for finding of optimum parameters of structure of network of power-supply with use the genetic algorithm.